Profil Komponen Volatil Beberapa Jenis Satai Menggunakan Kromatografi Gas - Muhammad Faqih Mukhlisin; Noviyan Darmawan; Dias Indrasti; Nancy Dewi Yuliana (Jurnal Ilmu Pertanian Indonesia, 2022)
Satay as Indonesian food is made from several pieces of meat stabbed with a bamboo stick and grilled. Satay has a unique aroma because of the diversity in total organic volatile contents. Differences in volatile compounds are also influenced by species breed and processing method. Volatilomics is a method used to ensure the authenticity of meat products through the detection, characterization, and quantification of all volatile metabolites in biological systems. This study aims to evaluate volatile profiles in beef, chicken, pork satay, and their mixtures. The volatile components of satay were extracted using the solid-phase micro extraction (SPME) method and analyzed using gas chromatography-mass spectrometry (GC-MS) instrument. Data were analyzed by multivariate principles component analysis (PCA). Beef, chicken, and pork satays were identified as having 104,134, and 112 volatile compounds, respectively. Nonanal was a volatile compound with the highest intensity in beef satay samples, benzaldehyde in chicken satay, and cyclohexanol in pork satay. Volatile components of satay with different types of meat showed good separation using the PCA model. Beef, chicken, and pork satays are grouped separately. Mixed-meat satay containing pork was grouped next to the pork satay. Volatilomic analysis identified a hexanal compound was potential to be used as a marker to distinguish between pork and other meat satays in halal authentication process. Keywords: beef, chicken, halal, pork, volatilomics